Hypopharyngeal Leishmaniasis: A case Report and Literature Review. - Elbalal, Moawia; M, Elgaili; Elawad, Izzalddinn; Mirghani, Hyder (Gezira Journal of Health Sciences, 2018)
Background: Leishmaniasis is classified into three clinical patterns: visceral, cutaneous and mucocutaneous.The latter are sporadically reported in Sudan and may not accompany the visceral type. Laryngeal symptoms including dysphagia may mimic oesophageal malignancy. Early detection and proper diagnosis are of great help in the cure and prognosis of the disease. Case report: We reported a case of primary isolated (the nasal mucosa was not involved) Hypophangeal Leishmaniasis in an immunocompetent Sudanese patient presenting with dysphonia, odynophagia and progressive dysphagia. Conclusion: Leishmaniasis should be suspected in all patients presenting with laryngeal symptoms in patients coming from endemic areas.